Analisis Yuridis Pemberian Bantuan Hukum Terhadap Tersangka/Terdakwa yang Berhadapan dengan Hukum Berdasarkan Ketentuan Pasal 56 Kitab Undang-Undang Hukum Acara Pidana (Studi Putusan Nomor: 619/Pid.B/2010/Pn.Sda dan Putusan Nomor: 899/Pid.Sus/2014/Pn.Dps) - Christiyanto, Rio; Artina, Dessy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Legal aid is the human rights of every person, who is not given by the state as the mercy of the state. The grant of legal aid is expected to be fair legal process for suspects or defendants who are poor and provide an opportunity to defend themselves with legal counsel. Guarantees of legal aid contained in Article 54 of the Criminal Procedure Code, which states, in the interests of defense, the suspect or the accused is entitled to legal assistance of one or more legal counsel during the time and at every level of examination, according to the procedures specified in this law. In addition, article 56 paragraph (1) Criminal Procedure Code that, in the case of a suspect or a defendant suspected of or charged with a criminal offense punishable by the death penalty or a penalty of fifteen years or more or for those who can not afford is punishable by five years or more who do not have their own legal counsel, the concerned officials at all levels of checks in the proceedings shall appoint counsel for them.The purpose of writing this thesis: First, to determine the legal consequences or effects when a suspect / defendant who deal with the law is not accompanied by legal counsel under the provisions of article 56 of the Criminal Procedure Code. Second, to determine the responsibility of the relevant authorities at every level of examination in providing legal assistance to the suspect / defendant against the law. normative research or the research literature, the type of research conducted by examining secondary law or research based on the standard rules that have been reflected and focused to study the principles of law, by searching various regulations in connection with the provision of legal assistance to suspects /defendant.From this study we can conclude: First, help law are rights of suspects or defendants in the interests of defense, guarantees protection and legal certainty and justice and equal treatment before the law that must be obtained from the level of inquiry, investigation, prosecution, trial and enforcement of the award. The legal consequences disregard for the rights of suspects / defendants get legal aid is null and void. Second, granting legal aid to the suspect / defendant an obligation concerned officials at every level of examination. Third, Indonesia adheres to regulations written law (Legal Positivism), where jurisprudence is not a necessity for the judge to obey. Suggestions Writer, implementation of legal assistance to the suspect / accused should be given at every level of examination is requested or not in order to attain justice and equality before the law.Keywords: Provision - Legal Aid - suspect - defendant